Distribution of 239, 240Pu in marine products from the seas around the Korean Peninsula after the Fukushima nuclear power plant accident. (June 2020) - Kim, Suk-Hyun; Lee, Sang-Han; Lee, Hyun-Mi; Hong, Gi-Hoon
Abstract: In March 2011, an earthquake caused the shutdown of the active reactors at the Fukushima Daiichi Nuclear Power Plant (NPP), with the succeeding tsunami resulting in the release of radioactively contaminated water into the adjacent Japanese coastal waters. Marine biota selected from various trophic levels were collected in Korean coastal waters throughout 2014 and 2015 and their plutonium levels were measured to evaluate the radioactive contamination levels in the marine organisms that constitute the primary seafood diet in the Republic of Korea (ROK). The results showed that the activity concentrations of 239, 240 Pu in plankton, macroalgae, mollusks, crustaceans, and cephalopods ranged from 13 to 58, 0.64 to 0.80, 0.94 to 5.40, 0.06 to 0.50, and 0.26 mBq kg −1 of wet weight (w.w.), respectively. The activity concentrations of 239, 240 Pu measured in the muscles of fish varied from 0.09 to 0.30 mBq kg −1 (w.w.), relatively low values compared to those in other groups regardless of fish species, size, and sampling area. The concentration characteristics of 239, 240 Pu in the various organs in the respective marine products revealed that the internal organs showed higher concentrations than the muscle or skin (or exoskeleton). The highest concentration of 239, 240 Pu was measured in the viscera of an abalone, which had an activity concentration of 6.31 mBq kg −1 (w.w.). The concentration factors (CFs) in the >300-μm fraction of plankton and in anchovy, shrimp, and mackerel ranged 67–84% of the International Atomic Energy Agency (IAEA)-recommended values, although the CF in macroalgae was much lower at approximately 5% of IAEA values, suggesting a wide range of 239, 240 Pu CF in macroalgae. The mean transfer factor (TF) between macroalgae (0.6–0.8 mBq kg −1 ) and abalone (5.4 mBq kg −1 ) was estimated to be 7.5, implying that effective Pu transfer occurred between the two species. These figures equate to annual effective doses of 239, 240 Pu to Koreans through consumption of macroalgae, shellfish, and fish of 1.8 × 10 −6, 1.4 × 10 −6, and 7.1 × 10 −7 mSv yr −1, respectively, and a total dose of 3.9 × 10 −6 mSv yr −1, values that are negligible compared to the annual effective dose limit of 1 mSv yr −1 . Highlights: The activity concentrations of 239, 240 Pu in fishery products detected in this study were not significantly different from those measured prior to the Fukushima NPP accident. The internal parts of fish had higher activity concentrations of 239, 240 Pu than the muscle or skin (or exoskeleton). The CFs of the > 300-μm fraction of plankton (i.e. zooplankton) and of anchovy, shrimp, and mackerel were found to be 67 to 84% of the recommended IAEA CFs for those groups of organisms. The total annual effective dose (3.9 × 10 −6 mSv yr −1 ) of 239, 240 Pu received through the consumption of fishery products was negligible in comparison to the 1 mSv annual dose limit set for the general public in the ICRP (2012).